Debating cognitive existentialism : values and orientations in hermeneutic philosophy of science - Ginev, Dimitŭr. (Value Inquiry Book Series, 2015)
Cognitive existentialism is a version of hermeneutic philosophy. The volume provides a summation of the critical approaches to this version. All essays are engaged in probing the value of universal hermeneutics. Drawing on various conceptions developed in analytical and Continental traditions, the authors explore the interpretative dimensions of scientific inquiry. They try to place the projects of their investigations in historical, socio-cultural, and political contexts. The task of extending hermeneutics to the natural sciences is an initiative of much relevance to the dialogue between the scientific and humanistic culture. A special aspect of this dialogue, addressed by all authors, is the promotion of interpretive reflexivity in both kinds of academic culture.